Kinetic Analysis and Pyrolysis Behavior of Pine Needles by TG-FTIR and Py-GC/MS - Langui Xu; Yujian Zhang; Ziyong Wang; Shurui Guo; Yongxing Hao; Yuguo Gao; Min Xin; Yi Ran; Shuxun Li; Rui Ji; Hongmei Li; Huixia Jiang; et al. (BioResources, 2023)
The pyrolysis performances and reaction kinetics of pine needles (PN) were investigated by integrating thermogravimetric analysis, Fourier transform infrared spectroscopy, and pyrolysis-gas chromatography/mass spectrometry. The average activation energy of PN was estimated to be 183.2 kJ/mol by Kissinger Akahira Sunose (KAS) and 183.8 kJ/mol by Flynn Wall Ozawa (FWO), respectively at heating rates of 10, 20, and 40 °C/min. The pyrolysis of PN was found to be more efficient at the lower heating rates, while increased heating rates promoted the reaction. Using the King-Kai (K-K) method, the activation energies of hemicellulose, cellulose, and lignin were calculated to be 156, 165, and 172 kJ/mol, respectively. The descending order of evolving gases and functional groups from PN was found to be CO2, C=C, C=O, H2O, CH4, and CO. The main pyrolytic by-products identified were hydrocarbons, phenols, alcohols, ketones, and aldehydes. The determination of kinetic parameters provides fundamental information for predicting the rates at which chemical reactions occur. This study demonstrates the potential of PN as a suitable source for bioenergy.